Pengembangan Simulator Sistem Bahan Bakar EFI (Electronic Fuel Injection) Sepeda Motor berbantuan QR Code bagi Guru dan Siswa Vokasi - Hidayat, Nuzul; Setiawan, M. Yasep; Muslim, Muslim; Sardi, Juli; Yanto, Doni Tri Putra; Afnison, Wanda (Jurnal Pendidikan Teknik Elektro, 2024)
Developing a QR Code-assisted simulator for Electronic Fuel Injection (EFI) systems aims to enhance teachers' and students' understanding of EFI technology in automotive education. EFI is a technology that electronically regulates vehicle fuel supply based on data collected from engine sensors. In practice, learning about EFI often requires expensive and hard-to-access physical equipment. Therefore, the QR Code-based simulator was developed as an innovative solution. This simulator enables students and teachers to access interactive content about the components and workings of the EFI system by scanning QR Codes linked to digital simulations. This approach makes the learning process more practical, interactive, and accessible. Research findings indicate that using this simulator significantly improves students' understanding of EFI concepts. Teachers also benefit from this tool, making teaching materials more engaging and comprehensible. This technology addresses the limitations of practical equipment, giving students a better opportunity to deeply understand EFI systems without relying on costly physical devices.